Techniques for the In Vitro Production of Queens in Stingless Bees (Apidae, Meliponini) - Baptistella, Ana Rita; Souza, Camila C. M.; Santana, Weyder Cristiano; Soares, Ademilson Espencer Egea (Sociobiology, 2014)
Considering the ecological importance of stingless bees as caretakers and pollinators of a variety of native plants makes it necessary to improve techniques which increase of colonies’ number in order to preserve these species and the biodiversity associated with them. Thus, our aim was to develop a methodology of in vitro production of stingless bee queens by offering a large quantity of food to the larvae. Our methodology consisted of determining the amount of larval food needed for the development of the queens, collecting and storing the larval food, and feeding the food to the larvae in acrylic plates. We found that the total average amount of larval food in a worker bee cell of F. varia is approximately 26.70 } 3.55 μL. We observed that after the consumption of extra amounts of food (25, 30, 35 and 40 μL) the larvae differentiate into queens (n = 98). Therefore, the average total volume of food needed for the differentiation of a young larva of F. varia queen is approximately 61.70 } 5.00 μL. In other words; the larvae destined to become queens eat 2.31 times more food than the ones destined to become workers. We used the species Frieseomelitta varia as a model, however the methodology can be reproduced for all species of stingless bees whose mechanism of caste differentiation depends on the amount of food ingested by the larvae. Our results demonstrate the effectiveness of the in vitro technique developed herein, pointing to the possibility of its use as a tool to assist the production of queens on a large scale. This would allow for the artificial splitting of colonies and contribute to conservation efforts in native bees.